Um olhar para manifestações matemáticas de crianças pequenas em situações de jogo na educação infantil - Piva, Ana Diva Rabuske (2024)
This dissertation presents a Master's degree research, linked to the Postgraduate Program in Mathematics Education and Physics Teaching at the Federal University of Santa Maria and is based on concerns that arose throughout the researcher's professional career when working with mathematics in the context of Early Childhood Education.The investigation was developed by looking at children's manifestations, in intentionally provoked moments of exploration of mathematical knowledge and driven by the question: How do children aged 4 to 5 years and 11 months express knowledge related to the mental processes of correspondence, comparison and classification in game situations? To better understand these processes, the general objective of the research was to investigate manifestations of children aged 4 to 5 years and 11 months related to the mental processes of correspondence, comparison and classification in game situations. In this context, an educational game called “Uncovering the secrets of the mini-farm” was designed and produced, in order to enhance and analyze children's manifestations based on 10 classes that were used for their development. The methodology has a qualitative approach and highlights children's interactions in intentional and game situations through data produced and recorded through observation and video recording of dialogues/interventions, photos and graphic records of children. From data analysis, the research shows that children's manifestations can indicate learning resulting from intentional situations linked to the game, as they explain knowledge related to different aspects of the mental processes of correspondence, comparison and classification. Furthermore, the possibility of carrying out pedagogical practices with intentionality stands out, emphasizing the importance of creating environments and game situations that are based on the assumptions of Historical-Cultural Theory as a way of bringing children closer to mathematical knowledge.